Comparison of the Implementation of the MBKM Curriculum in the Social Sciences Education Study Program at PTKIN in Indonesia - Mohammad Liwa Irrubai; Resti Kartika Dewi; Emilia Fatriani (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
This study examines the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy within Social Sciences study programs at State Islamic Religious Higher Education Institutions (PTKIN) in Indonesia. The research is motivated by the national importance of MBKM as a strategy to enhance the quality of higher education. At the same time, its application within PTKIN, particularly in the social sciences and religious studies, remains understudied and faces various practical challenges. This study aims to understand how MBKM is implemented, the factors that shape its execution, and its influence on teaching practices and graduate competencies. Using a qualitative approach, data were collected through in-depth interviews, observations, and document analysis in selected PTKINs. The findings reveal significant variation in MBKM implementation, influenced by institutional readiness, resource availability, and the involvement of lecturers and students. Despite obstacles such as curriculum adjustment and resistance to change, the study identifies positive outcomes, including enhanced learning creativity, improved practical skills, and greater curriculum relevance to industry and community needs.